2015
DOI: 10.1007/s00894-015-2709-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural-topological preferences and protonation sequence of aliphatic polyamines: a theoretical case study of tetramine trien

Abstract: A large set of lowest and medium energy conformers of aliphatic tetramine trien was used to uncover structural-topological preferences of poliamines. Numerous common structural features among HL and H 2 L tautomers were identified, e.g., H-atoms of protonated functional groups are always involved in intramolecular NH•••N interactions and they result in as large and as many as possible rings in lowest energy conformers. Largest, 11-membered, rings stabilize a molecule most and they appeared to be strain free wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Polyamines are extremely flexible molecules and often unexpected BPs are found in equilibrium structures 22 . Molecular graphs of protonated triethylenetetramine ( trien , HL) of (i) the lowest energy conformer (LEC; HL‐1) and (ii) the second lowest energy HL‐2 (with Δ E = E HL‐2 − E HL‐1 = 0.70 kcal/mol) found at the MP2 level are shown in Figure 1.…”
Section: Relative Molecular Stability and Highly Questionable Bpsmentioning
confidence: 99%
“…Polyamines are extremely flexible molecules and often unexpected BPs are found in equilibrium structures 22 . Molecular graphs of protonated triethylenetetramine ( trien , HL) of (i) the lowest energy conformer (LEC; HL‐1) and (ii) the second lowest energy HL‐2 (with Δ E = E HL‐2 − E HL‐1 = 0.70 kcal/mol) found at the MP2 level are shown in Figure 1.…”
Section: Relative Molecular Stability and Highly Questionable Bpsmentioning
confidence: 99%
“…It was necessary to employ MMFF(aq) because the sets of LECs discovered in the gas phase (using MMFF) were significantly different. This was done by a systematic variation of the torsional angle of each rotatable bond as described previously [40] with slight modifications implemented in the case of 3,2,3-tet (see PART 1 of the SI for a full description of the conformational search procedure used). We have also performed conformational search on the same ligands with explicitly added four water molecules which were placed (i) randomly in relation to their orientation toward a backbone structure of a ligand, but (ii) quite evenly along a molecule; for illustration, free ligands with water molecules are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…To this effect, we took advantage of having a large data bank from previous work [40] where hundreds of 2,2,2-tet conformers were fully optimised in Gaussian. A thorough inspection of the optimisation profiles generated for all tautomers of protonated forms of 2,2,2-tet revealed that in order to predict 'safely' the set of lowest energy conformers needed for the purpose of this study it would be sufficient to implement a pre-optimisation operation which involves terminating the optimisation process after 20 steps -for details see PART 4 in the SI.…”
Section: Pre-optimisation Protocolmentioning
confidence: 99%
See 2 more Smart Citations